The Two Way Symmetrical Model in Establishing Take and Give Relations with Community - Iin Masruroh (Yayasan Avicenna, 2023)
The purpose of this research was to describe the form of the two way symetrical communication model used by MA Subulus Salam in forming take and give relationships with the community. This research was conducted with a qualitative approach with a descriptive type. The data collection technique used was interviews with the Bureau of Education, Bureau of Islamic Boarding Schools, regional heads of West and East Islamic boarding schools, as well as documentation. Data analysis was carried out through three steps, namely: (1) data condensation; (2) data exposure; and (3) drawing conclusions and verification. Data validity with source and technique triangulation process. The two way symmetrical model that has been carried out by MA Subulus Salam includes several communication activities consisting of disseminating information among student parents, activating persuasive forms of business both directly and indirectly with the community, and analyzing every opinion of the school community and the madrasah community analytically and solutive. From this research reveals that through this communication technique to persuade (persuasive communication) to build mutual understanding, support and benefits from both parties. This model can also try to find a win-win solution in solving a problem.